Computer Simulation on Analgesic Functional Chemome Characteristics of Radix Saposhnikoviae - Chunsong ZHENG; Xiaojie XU; Hongzhi YE; Jinxia YE; Guangwen WU; Xianxiang LIU (康复学报)
Objective:To investigate analgesic functional chemome characteristics of Radix Saposhnikoviae (RS), and provide information on molecular basis for clinical application of RS in Bi syndrome therapy.Methods:The chemical components of RS were retrieved from the Handbook of the Constituents in Chinese Herb Original Plants and other literatures, and the molecular dataset of RS was constructed for computer simulation. Tumor necrosis factor alpha (TNF-α), p38, inducible nitric oxide synthase (iNOS) and phosphodiesterase 4A (PDE-4A) were considered as analgesic targets. The analgesic functional chemome of RS was identified by molecular docking. The drug/drug-like molecules correlated to p38, TNF-α, iNOS and PDE-4A were retrieved from therapeutic targets database (TTD). The analgesic functional chemome characteristics of RS were dissected by comparing the chemical space and compound-target network characteristics of the RS analgesic functional chemome to those of drug/drug-like molecules.Results:49 compounds, which mainly contained glycosides, flavonoids, coumarins, organic acids, etc., composed pharmacodynamic material basis of RS. These compounds had discrete chemical space, and most of them had similar chemical space with drug/drug-like molecules. The average target number correlated with each compound within the compound-target network was 1.20 in the analgesic functional chemome of RS and 1.05 in the drug/drug-like molecules, and each average target number was correlated with 12.25 compounds and 5.50 compounds, respectively. The number of compounds interacted with≥2 targets was eight in the analgesic functional chemome of RS and one in the drug/drug-like molecules.Conclusion:Computer simulation could intuitively trace out the analgesic function of RS. The functional chemome of RS had better multi-target effects compared with drug/drug-like molecules, and became an important source on mining promiscuous drugs from RS.